AUTOPOIESIS AND LIFE IN HEGEL’S SCIENCE OF LOGIC - Chaput, Emmanuel (Science et Esprit, 2023)
In this paper, I address the issue of Hegel’s Science of Logic as a self-producing system of thought developing itself through a process of self-contradiction and reconciliation. Such a process can be understood in a certain way as an anticipation of the notion of autopoiesis later developed by the biologists Humberto Maturana and Francisco Varela. The processualism and self-development of the concept through the progressive determination of logical categories, from the most abstract (or indeterminate) determinations of Being and Nothingness to the most concrete form of the concept should thus be read as the narrative of thought’s self-development as a form of life. Looking at Hegel’s logic through the lens of autopoiesis allows us to grasp the central importance of the ‘Life’ chapter of the Science of Logic as a hermeneutical device for the understanding of the logical process within the Logic.